2014
DOI: 10.4238/2014.september.5.5
|View full text |Cite
|
Sign up to set email alerts
|

Study of the correlation between GH gene polymorphism and growth traits in sheep

Abstract: ABSTRACT. The growth hormone gene plays an important role in the physiological function of an organism. The current study aimed to investigate the correlation between polymorphisms in the 5ꞌ regulatory region, exon 4, and 3ꞌ untranslated region (UTR) of the sheep GH gene and sheep growth traits. The DNA from 510 adult sheep was analyzed by DNA sequencing and polymerase chain reaction single-strand conformation polymorphism. Two alleles (A and B) and 3 genotypes (AA, AB, and BB), 2 alleles (A and B) and 3 genot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…Studies in other poultries reported the associations of the GH gene with growth and carcass traits in Pitalah and Kumbang Janti Indonesian ducks (Yurnalis et al, 2017), Huoyan Chinese native goose , and Japanese quail (Johari et al, 2013). In other farm animals, the GH gene was reported in cattle breeds (Dolmatova & Ilyasov, 2011), pig (Ashok et al, 2014), salmonids fish (Kamenskaya et al, 2015), sheep (Jia et al, 2014), goat , camel (Shawki et al, 2015), and passerine bird (Arai & Iigo, 2010). The effect of GH and GHR gene polymorphisms on carcass component in Kampung and broiler chicken cross has not been examined yet.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in other poultries reported the associations of the GH gene with growth and carcass traits in Pitalah and Kumbang Janti Indonesian ducks (Yurnalis et al, 2017), Huoyan Chinese native goose , and Japanese quail (Johari et al, 2013). In other farm animals, the GH gene was reported in cattle breeds (Dolmatova & Ilyasov, 2011), pig (Ashok et al, 2014), salmonids fish (Kamenskaya et al, 2015), sheep (Jia et al, 2014), goat , camel (Shawki et al, 2015), and passerine bird (Arai & Iigo, 2010). The effect of GH and GHR gene polymorphisms on carcass component in Kampung and broiler chicken cross has not been examined yet.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most remarkable features of the sheep GH gene is its extremely high degree of genetic polymorphism within loci (Jia et al, 2014). In previous studies on sheep, GH five SNPs were identified in the GH1/ GH2-N gene, three were located in the 5\ UTR and two in the 3\ UTR, compared to acc.…”
Section: Correlations and Regression Analysis Resultsmentioning
confidence: 99%
“…In the future, we intend to investigate the correlation between polymorphism and growth traits to identify suitable candidate markers that may be related to crustacean growth and development. The re sults presented herein could potentially lead to the use of genetic strategies for improved crab breeding (Jia et al, 2014).…”
Section: Discussionmentioning
confidence: 99%